2002
DOI: 10.1021/cm020007a
|View full text |Cite
|
Sign up to set email alerts
|

Thiol-Terminated Di-, Tri-, and Tetraethylene Oxide Functionalized Gold Nanoparticles:  A Water-Soluble, Charge-Neutral Cluster

Abstract: A series of gold nanoclusters stabilized by ligands containing short ethylene oxide oligomers of fixed length were prepared and characterized. The thiols CH3(OCH2CH2) n SH (where n = 2, 3, and 4) were substituted onto the surface of 1.8-nm hexanethiol-capped gold clusters by a thiol-exchange reaction, and the resulting nanoclusters were characterized by NMR, FTIR, and UV/vis spectroscopies; TGA; and TEM analysis. A degree of ligand exchange greater than 99% was achieved, and the gold core diameter remained unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
157
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(164 citation statements)
references
References 35 publications
6
157
1
Order By: Relevance
“…One popular approach is to modify nanoparticles with hydrophilic polymers {e.g., cyclodextrin (CD) [48,49], carbohydrates [26,50], peptide [16,51] and polyethylene glycol (PEG) [52][53][54]}. The polymer-capped nanoparticles show enhanced solubility in aqueous solutions and reduced cytotoxicity.…”
Section: Enhancing 1 H Nmr Resolution With Soluble Flexible Linkersmentioning
confidence: 99%
“…One popular approach is to modify nanoparticles with hydrophilic polymers {e.g., cyclodextrin (CD) [48,49], carbohydrates [26,50], peptide [16,51] and polyethylene glycol (PEG) [52][53][54]}. The polymer-capped nanoparticles show enhanced solubility in aqueous solutions and reduced cytotoxicity.…”
Section: Enhancing 1 H Nmr Resolution With Soluble Flexible Linkersmentioning
confidence: 99%
“…To address this issue, researchers have coated the nanocrystals with a wide array of alternative passivation agents, including phosphines, polymers, and proteins [25][26][27][28][29][30]. Within these categories, a wide variety of sizes of molecules may be used to passivate the gold surfaces.…”
Section: Gold Nanocrystal Surface Passivationmentioning
confidence: 99%
“…For example, Foos et al, reported a variety of ethylene oxide coated, charge-neutral gold nanocrystals that can be subsequently modified with thiols, including thiolated DNA [26]. Other work has shown neutral, polyethylene glycol (PEG) coated nanocrystals [36].…”
Section: Gold Nanocrystal Surface Passivationmentioning
confidence: 99%
“…Among these, tetraethylene glycol (TEG) is particularly attractive because it has been found to confer properties comparable to those of PEG in vitro, but with less impact on overall particle size. [5][6][7][8][9] Currently, no articles document the effect of this coat on nanoparticles in vivo. We here describe the results of experiments aimed at rectifying this absence using particles synthesized with a gold core to facilitate observation with both light microscopy (LM) and transmission electron microscopy (TEM).…”
Section: Introductionmentioning
confidence: 99%